Manajemen Pembinaan Club Eximble FC Jakabaring Palembang - Mutiara Fajar; Siti Ayu Risma Putri; Oktariyana Oktariyana; Muhsana El Chintami Lanos (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The problem in this research is how the management of coaching club exsimble jakabaring Palembang. This study aims to determine the management of Club exsimble Jakabaring Palembang development. This type of research is a qualitative descriptive study, using a survey method that is to collect as much data as possible about the achievements of Club Exsimble Jakabaring Palembang which is a supporter in this research. The informants in this study were 3 trainers and 15 athletes. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique uses data reduction methods, data presentation, and data verification. Based on the results of the research and discussion that has been stated above, the researcher can draw conclusions regarding the coaching of soccer achievements at the Exsimble club that the coaching carried out for both athletes and coaches has been directed and has been carried out in accordance with the stages of achievement sports coaching. This is evident from the achievements of athletes at Club Exsimble who excel at the city and provincial levels. In addition, support from the All-Indonesian Football Association (PSSI) of Palembang City also contributed to the progress of football in Palembang City, especially at Club Exsimble, both in terms of management organization, athletes, coaches, as well as facilities and infrastructure as well as support from parents.